[INVITED] Optical imaging and localization of prospective scattering labels smaller than a single protein. (January 2019) - Holanová, Kristýna; Vala, Milan; Piliarik, Marek
Highlights: The smallest scattering labels show potential for single particle tracking. Scattering objects as small as 2 nm are optically imaged. Position estimate is better than 10 nm. Extremely small scattering labels are ultimately photostable and biocompatible. Abstract: Labeling of biological matter is a key technique enabling visualization and real-time tracking of dynamic processes beyond the diffraction limit. While the precision of fluorescence-based localization microscopy is limited by signal saturation, a new generation of small scattering labels (such as gold nanoparticles) have brought the localization precision below the size of a single protein. However, the size of scattering labels is also the most obvious handicap, as they are usually significantly larger than the resulting localization precision. We address this inconsistency and demonstrate detection and precise localization of gold nanoparticles of only 2 nm in diameter using interferometric detection of scattering (iSCAT). This size is considerably smaller than the size of a small protein and in combination with the possibility of tracking the nanoparticle position, we foresee a new concept of detailed studies of biomolecular systems in the future.